Analytical Variations - Eight Critical Essays on Applied Music Theory - Edlund, Bengt (Methodology of Music Research, 2020)
This book gives a critical account of various methods used in music analysis. In the first chapter, a number of current approaches such as semiotics, musical implications, Schenkerian analysis, and generative theory are demonstrated on Mozart's K. 331 theme. Five essays deal with important concepts in music analysis: ambiguity, formal proportions, and similarity within and between works. A further chapter provides a discussion of probability, kinship, and influence - decisive criteria when judging musical plagiarism. The last essay, studying a piece by Schubert, sifts the prospects of deciphering a composer's sexual leanings from his music.